Association of Vertical Growth Pattern with Various Malocclusions Among Subjects Reporting to An Institutional Set Up - PATTURAJA, KIRUTHIKA; JAIN, RAVINDRA KUMAR; NASIM, IFFAT (The journal of contemporary issues in business and government, 2021)
Facial vertical growth pattern plays an important role in achieving facial balance as well as response to orthodontic treatment. Variation in growth pattern ,function of soft tissue and jaw musculature has an impact on dentoalveolar tissues thus influencing the pattern of malocclusion. The present study aims to identify the vertical growth patterns and its association with different malocclusion. A retrospective study was conducted using the case records of patients in a private University hospital between June 2019 to March 2020. The sample size consisted of a total of 225 patients based on malocclusion (class I -75 , class II - 75, Class III -75) whose data on age, gender, skeletal growth pattern were recorded. Frequency distribution and chi-square tests were applied for statistical analysis in SPSS 20.0. The study results showed that there is a statistically significant association between type of malocclusion and vertical growth pattern (p=0.026) vertical growth pattern was common in class II malocclusion. Also there was no statistically significant difference between vertical growth pattern and age (p= 0.524), gender (p=0.178). Hence it can be concluded that vertical growth pattern is not associated with age, gender but in subjects with class II malocclusion vertical growth pattern is more common than in other malocclusions.